Using Large-Scale Research to Gauge the Impact of Instructional Practices on Student Reading Comprehension: An Exploratory Study - Wenglinsky, Harold (Education Policy Analysis Archives, 2003)
Small-scale research has identified classroom practices that are associated with high student performance in reading comprehension. It is not known, however, whether these findings generalize to larger samples and populations, as most large-scale studies of the impact of teaching on student performance do not include measures of classroom practices. Generalizing to larger populations is particulary important at a time when policies national in their scope are calling for “scientifically-based” instruction in reading. The current study explores the possibility of using large-scale data and methods to study classroom practices in reading comprehension. It finds that such studies are both feasible and necessary. They are feasible insofar as it proved possible to collect and analyze data on classroom practices and student reading comprehension, and discern substantial effects of the one on the other. They are necessary insofar as the study confirmed the effectiveness of some classroom practices but not others. It therefore cannot be assumed that the findings of small-scale studies generalize to large populations.